2021
DOI: 10.5216/rpt.v50i2.67661
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and intensity of fish nematodes with zoonotic potential in the Brazilian Amazon, including a brief reflection on the absence of human infections

Abstract: This study aimed to characterize the prevalence, mean abundance, and mean intensity of potential fish-borne zoonotic nematode larvae infecting the predator fish Hoplias aff. malabaricus from the Tapajós River, in the municipality of Santarém, in the Brazilian Amazon. After capture, the specimens of H. aff. malabaricus were analyzed for infection by Contracaecum sp. and Eustrongylides sp. third-stage larvae, and the prevalence, mean abundance, and mean intensity were calculated. A literature search was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(54 reference statements)
2
1
1
Order By: Relevance
“…On average, seven L3 of Contracaecum were collected per fish and they were found freely in the body cavities, mesenteries, and muscle of fish. The results of the present study showed that the average number of larvae of Contracaecum parasite is similar to that of reported by Tesfaye et al [37] but higher than reported by Abdullah et al [18], Mitiku [35], and Lima et al [56] and lower than Corrêa et al's [76] report. Also, the average of five EMC of Clinostomum was recorded from Clinostomum infected fish, which is lower than reported by Bera et al [80], McAllister and Robison [81], and Aghlmandi et al [82], but higher than reported by Mitiku [35] and Mahdy et al [24].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…On average, seven L3 of Contracaecum were collected per fish and they were found freely in the body cavities, mesenteries, and muscle of fish. The results of the present study showed that the average number of larvae of Contracaecum parasite is similar to that of reported by Tesfaye et al [37] but higher than reported by Abdullah et al [18], Mitiku [35], and Lima et al [56] and lower than Corrêa et al's [76] report. Also, the average of five EMC of Clinostomum was recorded from Clinostomum infected fish, which is lower than reported by Bera et al [80], McAllister and Robison [81], and Aghlmandi et al [82], but higher than reported by Mitiku [35] and Mahdy et al [24].…”
Section: Discussionsupporting
confidence: 88%
“…Prevalence of Contracaecum in C. gariepinus in Lake Haramaya is almost similar with Mitiku [35] and Tesfaye et al [37], but lower than Amare et al [38], Lima et al [56], and Corrêa et al [76] and higher than Abdullah et al [18,77]. Prevalence of Contracaecum in O. niloticus in Lake Haramaya is also similar with Amare et al [38] but lower than Tesfaye et al [37], Reshid et al [39], Gebawo [40], and Necho and Awake [74] and higher than reported by Mitiku [35], Hailekiros et al [57], and Muluken [59].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations